EFEKTIVITAS CHITOSAN KULIT UDANG TERHADAP MASA SIMPAN IKAN GABUS ASIN (Ophiocephalus striatus) SEBAGAI PENGEMBANGAN MODUL PEMBELAJARAN KONSEP BIOTEKNOLOGI PANGAN PADA MATA KULIAH BIOTEKNOLOGI - Rahmi Elfitri Elfitri; Darmawati '; Elya Febrita Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research was to determine the effectiveness of chitosan shells on the shelf life of salted fish cork (Ophiocephalus striatus) in February and May 2015. The results are used to develop the concept of learning modules on the subjects of food biotechnology Biotechnology. This research was carried out by two phases: the field of research and development phase of learning modules. Research conducted experiments using completely randomized design (CRD) non factorial, which consists of 4 treatments and 3 replicates in order to obtain 12 experimental design. If there is a real test there will be a further test DMRT. The parameters observed water content, protein content, fat content, organoleptic color, aroma and texture. The results showed that administration of chitosan have a significant effect on water content, protein content and fat content in cork salted fish (Ophiocephalus striatus). Chitosan concentration of 2% is the best concentration. Where to lower the water content of 23.11%, amounting to 0.182% fat content can also increase the protein content of 60.95%. While the color and aroma of salted fish most preferred cork panelist in the treatment of 1.5% while the texture of the panelists preferred the treatment of 1%. Results of the study can be used as a learning module that is in the food preservative materials on subjects Biotechnology. Keywords: Effectiveness of Chitosan, Salted fish Cork, Learning Module.